Liveability analysis of gated and non-gated low middle income communities in kuala lumpur, Malaysia - Mohit, Mohammad Abdul; Sule, , Abass Iyanda (Centre for Research Initiative, Liberal Arts and Social Sciences. Universiti Sains Malaysia, 2015)
The aim of this paper is to examine the liveability conditions in gated and non-gated low middle income communities in Kuala Lumpur where rapid urban growth has led to many disruptions in the urban living environment. Hence, a livability framework was developed with dimensions from housing condition, economic condition, functional environment, social relations and community safety towards achieving the research objectives of – a) to study the liveability level in gated and non-gated communities, b) to compare the level of liveability between gated and non-gated communities, and c) to determine the dimensions and indicators which influence the level of liveability in both communities. Residents’ views were collected through a questionnaire survey which consisted of twenty-four indicators of liveability belonging to five dimensions from three communities in Kuala Lumpur. Two communities belong to non-gated and one community had gated living status. The findings of the research revealed that gated community has a better living conditions compared to the non-gated community. Thus, this research can be used as a turning point to improve the living environment of both gated and non-gated community